Gut microbes in cerebrovascular diseases: Gut flora imbalance, potential impact mechanisms and promising treatment strategies - Zou, Xuelun; Wang, Leiyun; Xiao, Linxiao; Wang, Sai; Zhang, Le (Frontiers in Immunology, 2022)
The high morbidity, mortality, and disability rates associated with cerebrovascular disease (CeVD) pose a severe danger to human health. Gut bacteria significantly affect the onset, progression, and prognosis of CeVD. Gut microbes play a critical role in gut-brain interactions, and the gut-brain axis is essential for communication in CeVD. The reflection of changes in the gut and brain caused by gut bacteria makes it possible to investigate early warning biomarkers and potential treatment targets. We primarily discussed the following three levels of brain-gut interactions in a systematic review of the connections between gut microbiota and several cerebrovascular conditions, including ischemic stroke, intracerebral hemorrhage, intracranial aneurysm, cerebral small vessel disease, and cerebral cavernous hemangioma. First, we studied the gut microbes in conjunction with CeVD and examined alterations in the core microbiota. This enabled us to identify the focus of gut microbes and determine the focus for CeVD prevention and treatment. Second, we discussed the pathological mechanisms underlying the involvement of gut microbes in CeVD occurrence and development, including immune-mediated inflammatory responses, variations in intestinal barrier function, and reciprocal effects of microbial metabolites. Finally, based on the aforementioned proven mechanisms, we assessed the effectiveness and potential applications of the current therapies, such as dietary intervention, fecal bacterial transplantation, traditional Chinese medicine, and antibiotic therapy.